The Effect of Post-Culture liquids of Antagonistic Fungi on the Healthiness and Yielding of Soybean - Alina Pastucha (Acta Agrobotanica, 2012)
The objective of the paper was to establish the protective effect of post-culture liquids of Trichoderma harzianum G 227 and Gliocladium fimbriatum G 156 for soybean against the soil-borne fungi. The use of those liquids for studies had a positive effect on the number, healthiness and yielding of soybean plants. Soybean seedlings were mainly infected by Pythium irregulare, Fusarium spp. and Rhizoctonia solani, while plants at anthesis were affected by Fusarium spp., Phoma exigua var. exigua, Rhizoctonia solani and Sclerotinia sclerotiorum. The use of post-culture liquids reduced the infection of plants by these pathogens.